Critical Pedagogy and Issue of Social Liberation: A Policy Perspective - Das, Dr. Pankaj (Voices of Teachers and Teacher Educators, 2021)
The need of the hour is to make our children more informed not only in terms of their pedagogical subject knowledge but also to critically engage themselves in their social surroundings. It is the place where they can try to build their future as socially efficient citizens. The critical engagement of school children with their social life demands a new transformative educational structure, different from the present existing educational structure. Here, the role of a teacher with a new curriculum model driven by the critical pedagogy of social liberation would be the only hope of transformation of an undesirable society to a desirable one. In this context, the National Curriculum Framework 2005 and National Education Policy 2020 emphasise the development of a new model of educational curriculum that is, a critical pedagogy. Thus, the onus of responsibilities lies on our teachers to develop critical thinking and problem-solving skills among school children with the help of proper guidance to assist them to ‘prepare for life’ in dynamic situations.